(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Children’s well-being has been a critical public health concern and an essential determinant of a nation’s overall growth. Although Government has initiated mid-day meal programs particularly in rural areas to improve school-age children’s health and nutrition, data on the nutritional status of sub-urban school children still remain limited. Objective: The present study investigated the nutritional profile of the children receiving mid-day meal (MDM) in a sub-urban school. Methodology: A descriptive, cross-sectional study was conducted among 181 school students of a suburban school in Chattogram. Students from Kinder Garten (KG) level to Class 5 (aged 5-16 years) were interviewed. Sociodemographic, anthropometric and data related to mid-day meal (MDM) were recorded and analyzed. Descriptive statistics were performed using Microsoft Excel. Results: The mean age of the participants was 9.43 ± 2.76 years. Most of them were girls (62.43%). The basal metabolic rates of day shift students (girls: 1154.817 kcal/day; boys: 1083.628 kcal/day) were consistently higher than those of morning shift students (girls: 1025.149 kcal/day; boys: 906.737 kcal/day), indicating age-related physiological differences. Height-for-age Z-scores revealed that 20.54% of girls and 8.68% of boys were stunted. BMI-for-age analysis indicated that 38.24% of boys and 32.77% of girls were underweight. Severe undernutrition (<−3 SD) was observed in 20.59% of boys and 13.27% of girls. Conclusion: The Mid-day meal (MDM) program in a school contributes to reduce hunger among the students during school period. In this study, 37.68% of boys and 33.04% of girls are underweight, and boys are more likely to suffer from mild to severe malnutrition by height for age and BMI for age metrics, despite getting MDM regularly. It is still insufficient to treat all nutritional issues. In order to determine the efficacy and long-term effects of school feeding programs in Bangladesh, the study emphasizes the necessity for future large scale research. Journal of Paediatric Surgeons of Bangladesh (2023) Vol. 14 (1 & 2): 24-30